MEMS switch contact bouncing mitigation using novel dual-pulse actuation voltage - Lai .C.H; Wong .W.S.H (Universiti Kebangsaan Malaysia, 2011)
A novel dual-pulse actuation voltage that reduces dielectric charging in micro-electromechanical system (MEMS) switch and thus leading to a longer switch lifetime, are shown to simultaneously mitigate MEMS switch contact bouncing. A simple mass-spring-damper mathematical model is used to simulate movement of the switch contact as the excitation voltage is applied. The model shows that the novel dual-pulse voltages damped the acceleration of the switch membrane as it approaches the contact point, eventually slowing it down and minimized the impact force. This has the effect of minimizing the occurrence of contact bouncing. Practical experiment on the commercial TeraVicta TT712-68CSP MEMS switch corroborates that the novel excitation voltages reduced bouncing